Concrete rapid repairing material based on microbial mineralization and preparation method and application thereof

By performing hydrophobic modification and vacuum impregnation technology on porous particles, microorganisms and nutrients are immersed into the particle pores, solving the problems of insufficient microbial activity and difficulty in diffusion of mineralized products, and achieving strong interface bonding, environmentally friendly and crack self-repairing effects of rapid concrete repair materials.

CN119707433AActive Publication Date: 2025-03-28SOUTHEAST UNIV

Patent Information

Application Number
CN202411872221.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Existing microbial-based concrete repair materials are insufficient in high alkaline environments, resulting in low mineralization and restoration efficiency, and the mineralized products inside porous particles cannot diffuse, making it impossible to effectively repair concrete defects.

Method used

Hydrophobically modified porous particles are used as carriers to immerse microorganisms, nutrients and calcium sources into the particle pores through vacuum impregnation, and aqueous epoxy is used to seal the particle pores to increase the bond between the particles and the cement matrix, and finally, it is composited with fiber composite mortar to make a concrete quick repair material.

Benefits of technology

It improves the microbial activity and diffusion ability of mineralized products, enhances the bonding strength of concrete interface, and achieves the improvement of crack self-repair and erosion resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a rapid concrete repairing material based on microbial mineralization as well as a preparation method and application of the rapid concrete repairing material. According to the method, hydrophobic modified porous particles are used as a carrier, microbial bacteria, nutrient substances and a calcium source with mineralization behaviors are soaked into pores of the porous particles through vacuum impregnation, the pores of the particles are properly sealed by adopting waterborne epoxy, and then the particles are packaged by using metakaolin and sodium silicate, so that the porous particles are obtained. And finally, compounding with fiber composite mortar to prepare the concrete rapid repairing material. The rapid concrete repairing material has the advantages of strong interface adhesion, environment friendliness, light weight, excellent surface compactness improvement effect, crack self-repairing and the like, and can be used for coating and repairing the defect surface of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete repair materials, and relates to a quick concrete repair material based on microbial mineralization, and a preparation method and application thereof. Background Art

[0002] Deterioration and damage of concrete materials are extremely common, which poses a huge safety hazard to structural engineering. Therefore, fast and high-performance repairs are of great significance to extending their service life. At present, crack repair materials and defect repair materials based on microorganisms generally have the following shortcomings: (1) The microorganisms are not active enough in the highly alkaline environment of concrete, resulting in low mineralization repair efficiency ([1] Zhu Fuhao. Experimental study on the acclimation of Bacillus pasteurianus and the solidification of aeolian sand in a high pH environment of steel slag [D]. Xinjiang Agricultural University, 2023. DOI: 10.27431 / d.cnki.gxnyu.2023.000127; [2] Cheng Wenfeng. Research on the performance of microencapsulated microorganisms in the self-repair of concrete cracks [D]. Shenzhen University, 2016; [3] Lai Xiaoying. Research on the effect of coral reef-immobilized microorganisms in the self-repair of concrete cracks [D]. Zhejiang Ocean University, 2022. DOI: 10.27747 / d.cnki.gzjhy.2022.000267.); (2) Although the porous particle immobilization method is used, Although it can effectively guarantee the activity of microorganisms, it also causes the mineralization products to accumulate inside the porous particles and cannot diffuse to play the role of mineralization repair ([4] Wei Shuangni, Wang Yinghui, Lai Junxiang, et al. Research progress of microbial self-repairing concrete [J]. Bulletin of the Chinese Ceramic Society, 2024, 43(08): 2737-2747+2757. DOI: 10.16552 / j.cnki.issn1001-1625.2024.08.001; [5] Hou Fuxing, Bai Yiming, Shen Di, et al. Research progress of carrier materials for microbial self-repairing concrete [J]. Journal of Materials, 2024, 38(13): 84-98; [6] Zhou Mengjun, Zhang Jiaguang, Li Zhu, et al. Experimental study on compressive strength of crack self-repairing concrete based on microbial mineralization deposition [J]. Concrete, 2018, (03): 35-39; [7] Wiktor, V. and Jonkers, HM, 2011. Quantification of crack-healing in novel bacteria-based self-healing concrete. Cement and concretecomposites, 33(7), pp.763-770.). Summary of the invention

[0003] The purpose of the present invention is to provide a concrete rapid repair material based on microbial mineralization and its preparation method and application. The concrete rapid repair material has the advantages of strong interface bonding, environmental friendliness, light weight, excellent surface compaction and self-repair of cracks, etc. It is in the form of powder, which becomes a viscous fluid when adding water, and can be coated to repair the defective surface of concrete.

[0004] The technical solution for achieving the purpose of the present invention is as follows:

[0005] The rapid concrete repair material based on microbial mineralization comprises porous particles encapsulating and carrying microorganisms and fiber composite mortar; the porous particles encapsulating and carrying microorganisms are prepared by the following steps:

[0006] (1) Hydrophobic modification of porous particles: ultrafine porous particles are added to water and mixed and stirred, a mixed solution containing a hydrophobic modifier and sodium hydroxide is added under heating conditions, and the particles are modified under stirring. After the modification is completed, the particles are filtered, washed, and dried to obtain hydrophobically modified porous particles;

[0007] (2) Preparation of microbial solution: After the microorganisms are expanded and cultured, the bacterial sludge is obtained by centrifugation, and the bacterial sludge is diluted to an OD600 value of 0.8, and then an aqueous epoxy emulsion and a curing agent are added to obtain a microbial solution;

[0008] (3) Immobilizing microorganisms: adding hydrophobically modified porous particles to a microorganism solution, evacuating the solution, and performing vacuum impregnation to allow the microorganism solution to penetrate into the pores of the porous particles. After the impregnation is complete, the solution is filtered and dried to obtain porous particles immobilizing microorganisms.

[0009] (4) Impregnation of nutrients and calcium sources: adding porous particles carrying microorganisms to a nutrient solution to which a calcium source is added, evacuating the solution, and performing vacuum impregnation. After the impregnation is complete, the solution is filtered and dried to obtain porous particles carrying microorganisms impregnated with nutrients and calcium sources;

[0010] (5) Encapsulation: After kaolin and sodium silicate are mixed in a mass ratio of 1:1, an equal mass of water is added, and the mixture is stirred evenly to form a slurry. The porous particles loaded with microorganisms that have been impregnated with nutrients and calcium sources are placed in the slurry for complete adsorption. After natural curing, the porous particles are dried to a constant weight to obtain porous particles encapsulating the loaded microorganisms.

[0011] Furthermore, in step (1), the ultrafine porous particles are selected from coral reef sand, ceramsite, expanded perlite, etc., with a fineness of 0.5 μm to 200 μm, and the fineness is normally distributed; the hydrophobic modifier is selected from fatty acids, stearic acid, oleic acid, etc.

[0012] Furthermore, in step (1), in the mixed solution containing the hydrophobic modifier and sodium hydroxide, the concentration of the hydrophobic modifier is 2.5% to 8%, and the concentration of the sodium hydroxide is 2% to 10%.

[0013] Furthermore, in step (1), the heating temperature is 60-80° C., and the modification time is more than 0.5 h.

[0014] Furthermore, in step (2), the microorganism is a microbial bacterium having mineralization behavior, and is selected from two or more of Bacillus pasteurianus, Bacillus cohnii and Bacillus subtilis.

[0015] Furthermore, in step (3) or (4), the pressure is evacuated to -0.07 MPa.

[0016] Furthermore, in step (4), the nutrients in the nutrient solution are yeast extract and glucose, and the calcium source is selected from calcium lactate, calcium chloride, etc.

[0017] Furthermore, in step (5), the adsorption time is 2 hours, the natural curing time is 24 hours, and the drying temperature is 45°C.

[0018] Furthermore, the fiber composite mortar is composed of cementitious material, fine aggregate, water reducing agent, fiber, water-based epoxy and water, wherein the water-cement ratio is 0.35, the mortar-sand ratio is 1:0.7, the mass ratio of cementitious material and porous particles encapsulating and immobilizing microorganisms is 1:1.3, the amount of water reducing agent is 1.8%, the amount of fiber is 0.4%, and the amount of water-based epoxy is 4%.

[0019] The fine aggregate described in the present invention is the fine aggregate conventionally used in mortar. Further, the fine aggregate is standard sand.

[0020] The cementitious material described in the present invention is a cementitious material commonly used in mortar. Further, the cementitious material is selected from low-alkalinity, fast-hardening cements such as magnesium phosphate cement or sulphoaluminate cement.

[0021] The fiber of the present invention is a fiber conventionally used in fiber composite mortar. Further, the fiber is selected from polypropylene fiber, polyethylene fiber, glass fiber or polyvinyl alcohol (PVA) fiber.

[0022] The water reducing agent described in the present invention is a water reducing agent commonly used in mortar. Further, the water reducing agent is selected from polycarboxylate water reducing agent.

[0023] The preparation method of the above-mentioned rapid concrete repair material based on microbial mineralization comprises the following steps:

[0024] The cementitious material, fine aggregate, water reducing agent, fiber, water-based epoxy and porous particles encapsulating and immobilizing microorganisms are stirred until they are uniformly mixed, the hydrophobic layer on the surface of the porous particles is ground off, and then water is added and stirred until they are uniformly mixed to obtain a concrete rapid repair material.

[0025] The invention also provides application of the above concrete rapid repair material in rapid repair of buildings.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] The present invention utilizes porous particles immobilized with microorganisms and fiber composite mortar to form a concrete rapid repair material, wherein the porous particles immobilized with microorganisms are treated with hydrophobicity, which has the following effects: (1) in actual application, since the porous particles are hydrophobic inside, the microbial mineralization products tend to diffuse to the hydrophilic environment outside the particles, and the particle immobilization will not restrict the mineralization repair and compacting effect; (2) the stability of the particle immobilization environment is increased, the microbial activity is improved, the pores at the interface of new and old concrete are compacted, and a long-term crack self-healing effect is achieved; (3) the hydrophobicity of the concrete surface is increased to a certain extent, thereby improving its anti-corrosion ability. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is described in detail below through the preferred embodiments of the present invention, but the following embodiments do not limit the protection scope of the present invention.

[0029] The present invention utilizes hydrophobically modified porous particles as carriers, impregnates microbial bacteria with mineralization behavior, nutrients and calcium sources into the pores of the porous particles through vacuum impregnation, and uses water-based epoxy to properly seal the particle pores, thereby increasing the adhesion between the particles and the cement matrix. The particles are then encapsulated with kaolin and sodium silicate, and finally compounded with fiber composite mortar to form a concrete rapid repair material.

[0030] Example 1

[0031] (1) 30 g of coral reef sand powder and 120 mL of water (mass-to-volume ratio of 1:4) were mixed and stirred, the temperature was kept constant at 80° C. in a water bath, and a mixture of 0.5 g / mL of stearic acid and 30 g / mL of sodium hydroxide was added. The mixture was stirred for half an hour, filtered and washed three times, and dried to obtain a hydrophobic treated coral reef sand powder.

[0032] (2) 3.0 g beef extract, 10.0 g peptone, 20 g urea, 5.0 g sodium chloride and 1 L water were mixed and stirred evenly, and the pH was adjusted to 7 with 1 mol / L sodium hydroxide solution, and sterilized by high pressure steam sterilization to obtain a sterile culture solution. Bacillus pasteurianus and Bacillus cohnii were inoculated into the cooled culture solution for expansion culture. The cultured strains were encapsulated into a centrifugal test tube for centrifugation to obtain bacterial sludge, which was diluted with water to an OD600 value of 0.8, and then an aqueous epoxy emulsion and 10% curing agent were added at a mass ratio of 1:1 to obtain a microbial solution.

[0033] (3) Pour the hydrophobic treated coral sand powder into the above-mentioned prepared microorganism solution, evacuate under -0.07 MPa environment, and vacuum immerse for 5 hours to allow it to penetrate into the pores of the coral sand. After filtering, place it in an environment of 35°C and dry it to constant weight.

[0034] (4) 40 g of yeast extract, 40 g of calcium lactate, 80 g of glucose and 1 L of water were mixed and stirred to prepare a nutrient solution, and the coral reef sand powder dried in (3) was immersed in the nutrient solution under a vacuum environment of -0.07 MPa for 5 h, and then taken out and dried in an environment of 40° C. to constant weight.

[0035] (5) Mix kaolin and sodium silicate in a mass ratio of 1:1, add an equal mass of water, stir evenly to form a slurry, place the dried coral reef sand powder in (4) in the slurry for adsorption for 2 hours, and then dry it in an environment of 45°C to constant weight after natural curing for 24 hours.

[0036] (6) Stir the cementitious material, fine aggregate, water reducing agent, fiber, water-based epoxy and the dried coral reef sand powder in (5) for 30 minutes, grind off the hydrophobic layer on the surface of the coral reef sand powder, then add water and stir until the mixture is uniform to obtain a concrete quick repair material. The cementitious material is sulphoaluminate cement, the fine aggregate is standard sand, the water reducing agent is a standard polycarboxylic acid water reducing agent, and the fiber is polyvinyl alcohol fiber. The water-cement ratio is 0.35, the cement-sand ratio is 1:0.7, the mass ratio of the cementitious material and the dried coral reef sand powder in (5) is 1:1.3, the water reducing agent and fiber content are 1.8% and 0.4% respectively, and the water-based epoxy content is 4%.

[0037] Comparative Example 1

[0038] This comparative example is substantially the same as Example 1, except that the mass ratio of the cementitious material to the dried coral reef sand powder in (5) is 1:1, and the cementitious material to sand ratio is 1:1.

[0039] Comparative Example 2

[0040] This comparative example is substantially the same as Example 1, except that the coral reef sand is not subjected to hydrophobic treatment.

[0041] Comparative Example 3

[0042] Pure sulphoaluminate cement fiber composite mortar was used as a blank control group, and the water-cement ratio, mortar-sand ratio, water reducing agent and fiber content, and waterborne epoxy content were the same as those in Example 1.

[0043] The concrete repair materials prepared in the embodiments and comparative examples were tested for their effectiveness through strength test, pore structure test and new-old concrete bonding strength test. The results are shown in Table 1.

[0044] Table 1

[0045] 3-point bending strength / MPa Porosity / % Bond strength of new and old concrete / MPa Example 1 9.2 11.0 7.1 Comparative Example 1 7.6 13.9 5.8 Comparative Example 2 7.5 16.6 5.2 Comparative Example 3 8.1 14.1 6.1

[0046] By comparing Example 1 and Comparative Example 1, it is found that reducing the amount of coral reef sand that immobilizes microorganisms will reduce the overall mechanical properties of the repair material, including the bending strength of the repair material itself and the bonding strength between new and old concrete, as well as the porosity. This shows that the addition of coral reef sand that immobilizes microorganisms plays an important role in compacting pores and improving mechanical properties.

[0047] By comparing Example 1 and Comparative Example 3, it is found that if the coral reef sand is not treated with hydrophobicity, the porosity, flexural strength and bonding strength of the new and old concrete of the repair material will decrease. This is attributed to the fact that the mineralization products of microorganisms immobilized in the coral reef sand are difficult to diffuse to the outside, resulting in almost no effect.

[0048] By comparing Example 1 and Comparative Example 4, it is found that after adding the coral reef sand with immobilized microorganisms, the inherent strength and repair performance of the repair material are increased, indicating that the microbial mineralization-based concrete rapid repair material of the present invention has application potential in the field of rapid building repair.

Claims

1. A rapid concrete repair material based on microbial mineralization, characterized in that: The method comprises porous particles encapsulating and immobilizing microorganisms and fiber composite mortar; the porous particles encapsulating and immobilizing microorganisms are prepared by the following steps: (1) Hydrophobic modification of porous particles: ultrafine porous particles are added to water and mixed and stirred, a mixed solution containing a hydrophobic modifier and sodium hydroxide is added under heating conditions, and the particles are modified under stirring. After the modification is completed, the particles are filtered, washed, and dried to obtain hydrophobically modified porous particles; (2) Preparation of microbial solution: After the microorganisms are expanded and cultured, the bacterial sludge is obtained by centrifugation. After the bacterial sludge is diluted to an OD600 value of 0.8, an aqueous epoxy emulsion and a curing agent are added to obtain a microbial solution; (3) Immobilizing microorganisms: adding hydrophobically modified porous particles to the microbial solution, evacuating the solution, and performing vacuum impregnation to allow the microbial solution to penetrate into the pores of the porous particles. After the impregnation is complete, filtering and drying are performed to obtain porous particles that immobilize microorganisms. (4) Impregnation of nutrients and calcium sources: adding porous particles carrying microorganisms to the nutrient solution to which the calcium source is added, evacuating the solution, and performing vacuum impregnation. After the impregnation is complete, filtering and drying are performed to obtain porous particles carrying microorganisms impregnated with nutrients and calcium sources; (5) Encapsulation: After kaolin and sodium silicate are mixed in a mass ratio of 1:1, an equal mass of water is added and stirred evenly to form a slurry. The porous particles loaded with microorganisms that have been impregnated with nutrients and calcium sources are placed in the slurry for complete adsorption. After natural curing, the porous particles are dried to a constant weight to obtain porous particles encapsulating the loaded microorganisms.

2. The concrete rapid repair material according to claim 1, characterized in that: In step (1), the ultrafine porous particles are selected from one or more of coral reef sand, ceramsite and expanded perlite, with a fineness of 0.5 μm to 200 μm and a normal distribution; the hydrophobic modifier is selected from fatty acids, stearic acid or oleic acid; in the mixed solution containing the hydrophobic modifier and sodium hydroxide, the concentration of the hydrophobic modifier is 2.5% to 8%, and the concentration of the sodium hydroxide is 2% to 10%; the heating temperature is 60 to 80°C, and the modification time is more than 0.5 h.

3. The concrete rapid repair material according to claim 1, characterized in that: In step (2), the microorganisms are selected from two or more of Bacillus pasteurianus, Bacillus cohnii and Bacillus subtilis.

4. The rapid concrete repair material according to claim 1, characterized in that: In step (3) or (4), the pressure is evacuated to -0.07 MPa.

5. The concrete rapid repair material according to claim 1, characterized in that: In step (4), the nutrients in the nutrient solution are yeast extract and glucose, and the calcium source is selected from calcium lactate or calcium chloride.

6. The concrete rapid repair material according to claim 1, characterized in that: In step (5), the adsorption time is 2 hours, the natural curing time is 24 hours, and the drying temperature is 45°C.

7. The concrete rapid repair material according to claim 1, characterized in that: The fiber composite mortar is composed of cementitious material, fine aggregate, water reducing agent, fiber, water-based epoxy and water, wherein the water-cement ratio is 0.35, the mortar-sand ratio is 1:0.7, the mass ratio of cementitious material and porous particles encapsulating and immobilizing microorganisms is 1:1.3, the dosage of water reducing agent is 1.8%, the fiber dosage is 0.4%, and the water-based epoxy dosage is 4%.

8. The concrete rapid repair material according to claim 7, characterized in that: The fine aggregate is standard sand, the cementitious material is magnesium phosphate cement or sulphoaluminate cement, the fiber is selected from polypropylene fiber, polyethylene fiber, glass fiber or polyvinyl alcohol fiber, and the water reducer is selected from polycarboxylate water reducer.

9. The method for preparing the concrete rapid repair material according to claim 7, characterized in that: The following steps are involved: The cementitious material, fine aggregate, water reducing agent, fiber, water-based epoxy and porous particles encapsulating and immobilizing microorganisms are stirred until they are uniformly mixed, the hydrophobic layer on the surface of the porous particles is ground off, and then water is added and stirred until they are uniformly mixed to obtain a concrete rapid repair material.

10. Use of the concrete rapid repair material according to claim 1 in rapid repair of buildings.

Citation Information

Patent Citations

  • Method for loading of microorganisms on multiphase biomaterials

    CA3149668A1

  • Microorganism self-restoring system for coal mine roadway anchoring sprayed concrete and construction method of microorganism self-restoring system

    CN107975385A

  • Method of manufacturing heat insulation board with microorganisms

    CN109704657A

  • Microbial immobilization method for self-repairing of concrete cracks

    CN111138107A

  • Self-repairing cement-based composite material as well as preparation method and application thereof

    CN113185206A

Cited By

  • Low-carbon repairing material for precast concrete component as well as preparation method and use method of low-carbon repairing material

    CN120328997A

  • Lightweight self-repairing concrete and preparation method thereof

    CN120398472A

  • Low-shrinkage high-adhesion concrete crack repairing agent and preparation method thereof

    CN122010524A